(untitled) (Scientific journal of the Fergana State University, 2024)
Annotation The article describes the results of research aimed at determining the impact of global climate warming on the vegetation processes of fruit trees. Vegetation processes of fruit trees were monitored in the Uychi district of the Namangan region from 2016 to 2020 using the field observation method. The observed results were compared with data on vegetation observations of fruit trees from 1946 to 1950, as documented in agrometeorological annals. The effect of climate warming on fruit tree vegetation was determined through data comparison.